Tracking labour market reforms in the EU member states : an overview of reforms in 2004 based on the LABREF database - Mourre, Gilles; Arpaia, Alfonso; Costello, Declan; Pierini, Fabiana; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2005)
The paper examines the rationale for creating a database on labour market reforms and looks at the value-added of LABREF compared with existing datasets. In doing so, it considers recent developments in the economic literature as regards the design of labour market institutions. After a description of the coverage and structure of the database and of the information contained therein, the paper provides a summary overview of reforms enacted by EU Member States in 2004. On the base of the qualitative information in the database, the paper builds simple indicators of reform intensity and makes a tentative characterisation of the reforms strategy implemented by the Member States in 2004.
Economic Papers